Joule-Thomson effect of AdS black holes in conformal gravity - Yang Guo; Hao Xie; Yan-Gang Miao (Nuclear Physics B, 2023)
We investigate the Joule-Thomson effect of AdS black holes in conformal gravity. We derive the Joule-Thomson coefficient in terms of thermodynamic relations and then make an alternative derivation via a direct way. We analyze the Joule-Thomson coefficient and find that the Joule-Thomson coefficients obtained from two different approaches are equal. Moreover, we present a novel isenthalpic process in which the inversion temperature is minimal and it separates the corresponding heating-cooling phase. We analyze the inversion temperature and its corresponding inversion curve that separates the regions for the JT effect to be allowable and forbidden, where such an effect can only be observed in the allowable region. We also discuss the effects of two important parameters on the inversion curves.